Rethinking the Social in Innovation and Entrepreneurship (Edward Elgar Publishing, 2024)
Offering a comprehensive classification of the analytical approaches to the social within the fields of innovation and entrepreneurship studies, this book showcases a wide variety of perspectives and a collection of theoretical analysis tackling social complexity.